Genomic investigation of colour polymorphism and phylogeographic variation among populations of black‐headed bulbul (Brachypodius atriceps) in insular southeast Asia. Issue 19 (4th August 2021) - Shakya, Subir B.; Haryoko, Tri; Irham, Mohammad; Suparno,; Prawiradilaga, Dewi M.; Sheldon, Frederick H.
Abstract: Intraspecific polymorphism in birds, especially plumage colour polymorphism, and the mechanisms that control it are an area of active research in evolutionary biology. The black‐headed bulbul ( Brachypodius atriceps ) is a polymorphic species with two distinct morphs, yellow and grey. This species inhabits the mainland and virtually all continental islands of Southeast Asia where yellow morphs predominate, but on two islands in the Sunda region, Bawean and Maratua, grey morphs are common or exclusive. Here, we generated a high‐quality reference genome of a yellow individual and resequenced genomes of multiple individuals of both yellow and grey morphs to study the genetic basis of coloration and population history of the species. Using PCA and STRUCTURE analysis, we found the Maratua Island population (which is exclusively grey) to be distinct from all other B . atriceps populations, having been isolated c. 1.9 million years ago (Ma). In contrast, Bawean grey individuals (a subset of yellow and grey individuals on that island) are embedded within an almost panmictic Sundaic clade of yellow birds. Using F ST and d xy to compare variable genomic segments between Maratua and yellow individuals, we located peaks of divergence and identified candidate loci involved in the colour polymorphism. Tests of selection among coding‐proteins in high F ST regions, however, did not indicate selection on the candidate genes. Overall, we report on some loci that are potentially responsible for the grey/yellow polymorphism in a species that otherwise shows little genetic diversification across most of its range.